Towards seamless source mobility in SSM: design and evaluation of the Tree Morphing protocol - Olaf Christ and Thomas C. Schmidt and Matthias Wählisch (International journal of internet protocol technology, 2009)
Multimedia networking in the near future is expected to be dominated by group applications such as IPTV, MMORPGs, and video conferencing. Hand in hand with new service offers, the deployment of multicast at the network layer started to disseminate. Currently infotainment is gradually expanding into the mobile world, but a standard design of mobile multicast is still awaited. In this paper we present a design and discuss an extensive evaluation of the Tree Morphing Protocol that performs an adaptive tree management to support seamless handovers for mobile SSM sources. Based on a full protocol implementation on a network simulator platform, we extensively explore the protocol performance. By employing artificial networks to cover fundamental topological constellations, as well as real-world network topologies, we analyze the handover behavior conceptually and in realistic scenarios. Strengths and weaknesses of the routing scheme are identified, leading to a discussion on future improvements.
Keywords: mobile source specific multicast; route optimisation; mobile IPv6; protocol performance; verification; simulation; source mobility; tree morphing protocol; handover behaviour; multimedia networking